Preparation of a cross-linked cartilage acellular-matrix film and its in vivo evaluation as an antiadhesive barrier - Park, Joon Yeong; Song, Bo Ram; Lee, Jin Woo; Park, Seung Hun; Kang, Tae Woong; Yun, Hee Woong; Park, Sang Hyug; Min, Byoung Hyun; Kim, Moon Suk (Polymers, 2019)
In this paper, a cartilage acellular-matrix (CAM) is chosen as a biomaterial for an effective antiadhesive barrier to apply between injured tissue and healthy tissues or organs. CAM is cross-linked using glutaraldehyde to create a cross-linked CAM (Cx-CAM) film. Cx-CAM has higher elastic modulus and toughness and more hydrophobic surface properties than CAM before cross-linking. Small intestinal submucosa (SIS), cross-linked SIS (Cx-SIS) as a negative control, and Seprafilm as a positive control are used in an experiment as adhesion barriers. Human umbilical vein endothelial cells (HUVECs) on SIS, Cx-SIS, or in a culture plate get attached and effectively proliferate for 7 days, but Cx-CAM and Seprafilm allow for little or no attachment and proliferation of HUVECs, thus manifesting antiadhesive and antiproliferative effects. In animals with surgical damage to the peritoneal wall and cecum, Cx-CAM and Seprafilm afford little adhesion and negligible inflammation after seven days, as confirmed by hematoxylin and eosin staining and macrophage staining, in contrast to an untreated-injury model, SIS, or Cx-SIS film. Cx-CAM significantly suppresses the formation of blood vessels between the peritoneal wall and cecum, as confirmed by CD31 staining. Overall, the newly designed Cx-CAM film works well as an antiadhesion barrier and has better anti-tissue adhesion efficiency.
Keywords: Acellular matrices; Adhesion barrier; Anti-adhesive; Antiproliferative effect; Human umbilical vein endothelial cells; Hydrophobic surfaces; Small intestinal submucosa; Tissue adhesion; Antiadhesive film; Cartilage acellular matrix; Cross-linking; Tissue adhesion